Internalization of Ulil Albab Values in Character-Based Islamic Education - Pebrian Yoza Pratama; Galih Dwi Ramadhan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to analyze the internalization of ulil albab values within character-based Islamic education through a literature review approach. The concept of ulil albab, rooted in the integration of dhikr, intellectual reflection, and righteous action, is considered highly relevant as a foundation for character formation. By reviewing scholarly works, Qur’anic exegeses, and previous research, this study finds that the internalization of ulil albab values strengthens students’ moral, spiritual, intellectual, and social dimensions. The internalization process becomes effective when implemented through teacher role modeling, habituation, curriculum integration, and the development of a religious school culture. The findings indicate that Islamic education that harmonizes intellectual reasoning and spiritual awareness can cultivate students who are ethical, critical, and possess strong integrity. Therefore, ulil albab values serve not only as a theological framework but also as a practical guideline for character-building in Islamic educational institutions. This study is expected to provide theoretical and practical contributions to the development of Islamic education models relevant to contemporary challenges